The Influence of Bleeding Direction on Starting Performance of Three-Dimensional Inward Turning Inlet - Tianyu Gong; Yiqing Li; Feng Wei; Shiqichang Wu; Dehua Cao (International Journal of Aerospace Engineering)
Bleeding is an effective method to improve the starting performance of the inlet, and the conventional method often adopts the bleeding to longitudinal direction. This article proposes the use of transversal bleeding method to explore the influence on starting capacity by changing the bleeding direction. The paper designs 6 bleeding inlets. By calculating the starting performance, it is found that the projected bleeding rate of the inlet, which is the direct factor influencing the starting performance, would change due to the direction change of bleeding, although designed with the same entrance. For the inlet designed with longitudinal slots and bleeding, it could reach the starting state at Mach 3.6, but it showed the unstart state when they are transversal direction. The same entrance, when inlet is designed by transversal bleeding with longitudinal slots, the starting Mach number would decrease to 3.8. For the changes of aerodynamic capabilities, there would be the “point jump” tendency when reaching starting state, but the same inlets would keep the similar performance when they get the starting state.